Enhanced hydration model of fly ash in blended cement and application of extensive modeling for continuous hydration to pozzolanic micro-pore structures. (November 2020) - Kinomura, Koji; Ishida, Tetsuya
Abstract: Fly ash (FA) concrete has many advantages of enhancing durability even in severe environmental conditions. If the long-term performance can be predicted with higher reliability, it greatly contributes to determination of proper mix proportions in structural design, with further application to practical structures being anticipated. Although the finding that peculiar slow-down hydration of FA in blended cement occurs according to the experimental conditions had been pointed out, the original multicomponent hydration model in DuCOM was not able to simulate a similar tendency. Hence, by simply considering morphology and intrinsic properties of precipitated C-S-H gels due to pozzolanic reactions, an enhanced hydration model was proposed. In addition, the original models, regarding compressive strength development and continuous hydration considering spatial condensed water in fine micro-pore structures, were extended to be applicable also to FA blended cement. Verification of the installation effect was revealed through good agreement with the peculiar experimental tendency.